Behavioural ecology and management of Hihi (Notiomystis cincta), an endemic New Zealand honeyeater : a thesis presented in partial fulfilment of the requirements for the degree of PhD in Ecology at Massey University - Castro, Isabel (Massey University, 1995)
This thesis is concerned with the release techniques, post-release survival and behavioural ecology of hihi (Notiomystis cincta), a rare New Zealand honeyeater. It aims at offering management strategies for translocated populations. The only self-sustaining population of hihi exists on Little Barrier Island. The New Zealand Department of Conservation is trying to establish self-sustaining populations elsewhere. In 1991 and 1992 hihi transfers to Kapiti Island were approached in an experimental way. Experiments provided four main conclusions: (1) immediate-release birds survived better than delayed-release birds; (2) there was no difference between the survival of birds released in pairs or in a group; (3) hihi released in the absence of resident conspecifics survived better than those released in their presence; and (4) birds released in the absence of resident conspecifics moved to an area with residents in three days. The breeding system of hihi is highly variable, including monogamy, polyandry, polygyny and polygynandry. Males have physical features found in other species with highly variable mating systems. Male and female hihi benefit from a mixed reproductive strategy where a female hihi can solicit copulations from males other than her partner and male hihi can perform extra-pair copulations both with willing females or by forced copulation. Field tests aimed at determining the influence of the distribution of food and nest sites on the choice of mating system by hihi are proposed. The phenology of a selected group of plants, important as honeyeater food, was followed from 1992 to 1994. The onset and length of the flowering and fruiting periods for particular plant species varied between the years. The number of fruits and flowers per tree also varied. Hihi egg laying periods coincided with the period of greatest flowering. Hihi breeding success was low every year. In 1993-94 there was great competition for nest sites with kakariki Cyanoramphus novaezelandiae. It is suggested that hihi failure to establish self-sustaining populations on Kapiti Island is mainly the result of competition for nest sites and food limitation. It is recommended that feeding stations and nesting boxes are established in three different areas of the island. Food should be provided during the breeding season. The quality of nectar in some small flowers, and the rate of flower visitation by hihi, tui Prosthemadera novaezelandiae and bellbirds Anthornis melanura to those flowers were measured. The estimated nectar consumption rate for all flowers was enough to sustain hihi and bellbirds' energetic requirements. It is suggested that honeyeaters might play a previously unrecognised but important role in pollination. Forest regeneration on the New Zealand mainland could be hampered by the loss of hihi and serious reduction in the abundance of tui and bellbirds. Necessary studies to elucidate the role of honeyeaters in pollination are offered.
Keywords: Hihi; Notiomystis cincta; New Zealand honeyeater; Honey eaters; Birds; Ecology; New Zealand